Age modulates, religious coping mediates: the role of attitude to self in cancer patients’ quality of life - Onyedibe, Maria-Chidi C.; Chidebe, Runcie C.W.; Andersen, Barbara L.; Ugwoke, Uzoamaka F.; Ugwu, Lawrence Ejike (Frontiers in Psychology, 2025)
BackgroundCancer significantly impacts psychological well-being and health-related quality of life (HRQoL). This is particularly evident in low and middle-income countries (LMICs) where healthcare disparities exacerbate distress. Cognitive vulnerabilities, including negative generalization, self-criticism, and high standards, may influence HRQoL through their effects on coping mechanisms. Religious coping, shaped by cultural norms in LMICs, may mediate these relationships, with age as a potential moderator.ObjectiveThis study examines how attitudes toward self (ATS), religious coping, and age influence HRQoL among cancer patients in an LMIC context.MethodsA cross-sectional study of 565 cancer patients in a University Teaching Hospital, Southwest Nigeria completed a standardized and validated self-report measures of ATS, HRQoL, and religious coping. Mediation and moderation analyses were conducted using SPSS (Version 29) and SmartPLS (Version 4).ResultsNegative generalization (β = −0.25, p < 0.001) and self-criticism (β = −0.19, p < 0.001) reduced physical well-being, while high standards positively influenced emotional well-being (β = 0.27, p < 0.001) but negatively impacted functional well-being (β = −0.13, p < 0.01). Negative religious coping (NRC) mediated the relationships between ATS and HRQoL, amplifying negative effects on physical (β = −0.25, p < 0.001) and functional well-being (β = −0.32, p < 0.001). Age moderated these relationships, with older patients showing sharper declines in physical (β = −0.09, p < 0.01) and functional well-being (β = −0.10, p < 0.01). Positive religious coping had limited effects.ConclusionThe study highlights the significant impact of cognitive vulnerabilities and maladaptive religious coping on the HRQoL of older cancer patients in LMICs. These findings underscore the urgent need for tailored interventions that integrate cognitive-behavioral therapy (CBT) with culturally and religiously sensitive approaches to improve patient outcomes. Policymakers and healthcare providers should prioritize training and resource allocation to address these challenges. Future research should focus on longitudinal patterns of coping, as well as gender-related differences, to develop more inclusive and effective strategies for enhancing the well-being of cancer patients.